The Role of SME Human Capital Resource Competence in Improving SME Performance - Alatas, Rahman; Mohdari; Ady Kurnia (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
Small and Medium Enterprises (SMEs) play a crucial role in the economies of many countries, including Indonesia. However, one of the main challenges they face is improving business performance amidst increasing competition. This study aims to examine the impact of human resource (HR) competencies on the performance of SMEs. HR competencies include the abilities, knowledge, and skills possessed by employees to perform their tasks effectively. This research utilized a quantitative approach with a survey design and employed Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data were collected from 100 SME owners or managers in Macassar using questionnaires. The findings indicate that HR competencies have a significant positive effect on various performance indicators such as sales growth, profitability, operational efficiency, and customer satisfaction. The study highlights the importance of investing in education, training, and continuous development of HR competencies to enhance SME performance. Furthermore, the results suggest that improved HR competencies can foster innovation and adaptability in SMEs, contributing to their competitiveness in a dynamic market environment. This research provides valuable insights for policymakers and SME managers on the critical role of HR competencies in driving business success.